PENGARUH KUALITAS PELAYANAN DAN KINERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT PADA PELAYANAN KTP ELEKTRONIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KARANGANYAR: PENGARUH KUALITAS PELAYANAN DAN KINERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT PADA PELAYANAN KTP ELEKTRONIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KARANGANYAR - Santoso, Eko Agus; Haryanto, Aris Tri; Suryo Sarjono, Herning (JI@P, 2023)
The development of service quality and community demands for quality services, currently there are still many complaints from the public in the e-KTP service at the Population and Civil Registration Service in Karanganyar Regency. The purpose of this study was to determine the effect of service quality and employee performance partially and simultaneously on community satisfaction in the Electronic ID card service at the Population and Civil Registration Office of Karanganyar Regency. This type of research is a quantitative approach. The research sample is 100 community respondents who use e-KTP services. Data collection techniques using questionnaires, documentation, and literature study. The hypothesis testing technique uses Multiple Regression Analysis, t test, F test, and the coefficient of determination (R2). Based on the results of research and data analysis, this study can be concluded that the quality of service and performance partially and simultaneously affect public satisfaction with the Electronic ID card service at the Population and Civil Registration Office of Karanganyar Regency. Keywords: Service Quality, Performance, Public Satisfaction